Unequivocal identification of two-bond heteronuclear correlations in natural products at nanomole scale by i-HMBC - Wang, Yunyi; Fan, Aili; Cohen, Ryan D.; Dal Poggetto, Guilherme; Huang, Zheng; Yang, Haifeng; Martin, Gary E.; Sherer, Edward C.; Reibarkh, Mikhail; Wang, Xiao (Nature communications, 2023)
HMBC is an essential NMR experiment for determining multiple bond heteronuclear correlations in small to medium-sized organic molecules, including natural products, yet its major limitation is the inability to differentiate two-bond from longer-range correlations. There have been several attempts to address this issue, but all reported approaches suffer various drawbacks, such as restricted utility and poor sensitivity. Here we present a sensitive and universal methodology to identify two-bond HMBC correlations using isotope shifts, referred to as i-HMBC (isotope shift detection HMBC). Experimental utility was demonstrated at the sub-milligram / nanomole scale with only a few hours of acquisition time required for structure elucidation of several complex proton-deficient natural products, which could not be fully elucidated by conventional 2D NMR experiments. Because i-HMBC overcomes the key limitation of HMBC without significant reduction in sensitivity or performance, i-HMBC can be used as a complement to HMBC when unambiguous identifications of two-bond correlations are needed. The inability to distinguish two-bond from long-range HMBC correlation has historically impeded NMR structure elucidation. Here the authors developed a practical iHMBC methodology utilizing accurate isotope shift measurement to overcome this limitation.